Rethinking activist educational research: definitions, methodologies, and ethics. Issue 2 (15th March 2021) - Nguyen, Nicole
ABSTRACT: In this article, I revisit the concept of activist educational research to consider a wider array of methodological approaches that support the documentation and transformation of systems of oppression, from youth participatory action research projects to 'studying up.' Although activist researchers often turn to participatory methods, I examine how 'studying up' can support grassroots organizing from below. Drawing on my own experiences 'studying up' to better understand how emerging national security policies have criminalized Muslim youth, I analyze the methodological considerations, ethical provocations, and accountability processes such projects raise. By (re)broadening what counts as activist educational research using the rubric of transforming existing social arrangements and reaffirming the feminist concept of 'strong objectivity' (Harding, 1995), I encourage education scholars across the globe to engage a broader range of methodological approaches to support community struggles for educational justice.